Effect of Relative Humidity and Temperature on Airborne Venezuelan Equine Encephalitis Virus - Ehrlich, Richard (Appl Microbiol, 1971)
Inactivation of airborne Venezuelan equine encephalitis (VEE) virus disseminated from liquid suspensions or from lyophilized preparations as 1- to 5-μm particles was investigated under various conditions of relative humidity and temperature in a 2,500-liter static aerosol chamber. Relative humidity ranging from 18 to 90% at 24 C and temperature ranging from −40 to 24 C had no marked effect on the biological decay rate or the recovery of viable airborne VEE virus disseminated from liquid suspensions. However, at 49 C a significant increase in the biological decay rate and decrease in aerosol recovery of the VEE virus were observed. Airborne lyophilized VEE virus was significantly affected by relative humidity. An increase in relative humidity from 20 to 90% resulted in progressive decrease in aerosol recovery of viable VEE virus. A twofold reduction in aerosol recovery of the lyophilized virus was observed at and above 29 C as compared to the lower temperatures studied. However, the differences among biological decay rates of lycphilized VEE virus were not significant within temperature range of −40 to 38 C.